Cos (B) = (a^2 + c^2 -b^2) / (2 * a * c)
cos (B) = (11^2 +17^2 -12^2) / (2 * 11 * 17)
cos (B) = (121 + 289 -144) / (374)
cos (B) = 266 / 374
cos (B) =
<span>
<span>
<span>
0.7112299465
Angle B = </span></span></span>44.665 degrees
I don't see any diagram. So, I'll just wing it.
Value of q:
p, 6, 9 ⇒ there is a difference of 3. The sequence increases by 3. So, it can be assumed that the p is equal to 3. A(p,4) ⇒ A(3,4)
Value of q:
4, 1, q ⇒ there is a difference of 3. The sequence decreases by 3. So, it can be assumed that q is equal to -2. C(9,-2)
p q
A 3 4 ⇒ 3 + 4 = 7
B 6 1 ⇒ 6 + 1 = 7
C 9 -2 ⇒ 9 + (-2) = 7
Notice that the sequence has an equation of p + q = 7.
If you flipped the graph y=x^2+2x-2 vertically, you would get the graph y=-(x^2+2x-2) this is True.